PENGARUH CAPITAL ADEQUACY, LIQUIDITY RATIO, CREDIT RISK, OPERATIONAL EFFICIENCY, DEBT TO EQUITY RATIO DAN UKURAN PERUSAHAAN TERHADAP PERTUMBUHAN LABA BANK - Rispantyo, Setya Budi Harsana, Y. Djoko Suseno & (Universitas Slamet Riyadi, 2018)
The purpose of this research is to analyze the significance effect ofcapital adequacy ratio, credit risk, operational efficiency, debt to equity ratioand size to bank profit growth. This type of research is empirical research ata conventional bank in Indonesia Stock Exchange. Sample 29 banks withpurposive sampling. Sources of data used secondary data in the form offinancial statements of banks listed in BEI period 2012 – 2016. Methods ofdata collection used documentation.Teknik data analysis used multiple linearregression. The results showed that the Capital Adequacy Ratio has nosignificant efffect on bank’s profit growth. Liquidity ratio has no significanteffect on bank profit growth. Credit risk has a significant effect on bank’sprofit growth. Operational efficiency has a significant effects on bank’s profitgrowth. Debt to equity ratio has no significant effect on bank’s profit growth.The firm size has a significant effect on bank’s profit growth.Keywords: CAR, liquidity ratio, credit risk, operational efficiency, DER, firmsize, profit growth